Adequacy and Factors Associated with Recruitment Corresponded with Educational Qualification of Public Health Professionals of Local Administrative Organization in Thailand - Sornlorm, Kittipong; Laohasiriwong, Wongsa; Sara, Riski; Charoenpon, Supot; Timtub, Anek; Tiatrakul, Yangyuen; Kumkor, Saksith; Jitaram, Parinya; Hnuploy, Kanit (Health Science Journal of Thailand, 2022)
This cross-sectional study aimed to describe the situation of sufficiency and demand for public health personnel. Including identifying factors associated with recruitment corresponded with educational qualification and policy recommendations on production and demand for quality development were later identified. A total of 511 local administrative organization (LAO) administrators were multi-stage random sampling. The questionnaire was used to collect data and was analyzed by descriptive statistics to describe the situation and logistic regression analysis was used to identify the associations. The study result found that the administrators of the LAO still needed personnel who were public health professionals. 47.94 % of LAO had insufficient public health technical officers and 50.29% of public health officers according to the human resources framework. The factors associated with recruitment corresponded with the educational qualification of a public health professionals at LAO were: has had scholarships for public health students (AOR = 4.22, 95%CI: 1.82– 9.82), has a plan for new public health technical officer positions (AOR = 3.26, 95%CI: 2.08–5.13), has needs for accounting, financial and supplies competencies (AOR = 3.17, 95%CI: 2.00–5.04), needs for research competency (AOR = 2.27, 95%CI: 1.46–3.55), needs for information technology competency (AOR = 2.15, 95%CI: 1.37–3.37) and needs communicable disease control and disaster management competencies (AOR = 2.09, 95%CI: 1.26–3.48). LAO should have strategic workforce planning, especially for public health professionals to solve and prevent manpower shortage problems.